Conjugation of Triterpenic Acids with 3-Aminoquinuclidine Moiety: An Approach to Acetylcholinesterase Mixed or Uncompetitive Type Inhibitors - Anastasiya V. Petrova; Ha T. T. Nguyen; Irina V. Zueva; Konstantin A. Petrov; Alexander N. Lobov; Oxana B. Kazakova (Molecules)
Alzheimer’s disease (AD) poses a significant public health issue. Despite the fact that today there are several methods of maintenance therapy, one of the most widely used methods is designed to correct the deficiency of acetylcholine. In the search for new potential inhibitors of cholinesterase enzymes, eight new derivatives of 3-oxo- or 2,3-indolo-triterpenic acid conjugated with amino-quinuclidine bicyclic cores were designed and synthesized. Then, the obtained compounds were screened in Ellman’s assays for their ability to inhibit acetylcholinesterase enzyme, and for each of the active compounds, the type of inhibition was determined. The obtained results demonstrate the dependence of the activity on the triterpenoid structure and the type of substituents. The best activity for ursolic acid derivatives was observed for the 3-oxoamide 8, with an IC50 value of 0.43 µM, acting as a mixed-type inhibitor. In turn, for the oleanane type, the amide with an indole unit in the A ring 11 exhibited the best activity with an IC50 value of 0.47 µM (while the ursane-type analog was weakly active) and led to an uncompetitive type of inhibition. Thus, 3-amidoquinuclidine-triterpenoids conjugates could be considered novel inhibitors of acetylcholinesterase with a different mechanism of action.